Launching Blockchain Startups in Southeast Asia : A Comparative Study of Legal, Business, and Market Challenges and Opportunities - Zverev, Nikita; Abdallah, Kareem Issam; Jedlinský, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor’s thesis aims to identify and comparatively evaluate the most suitable countries in Southeast Asia for launching blockchain startups. The theoretical part of the thesis provides an overview of blockchain technology, startup ecosystems, and the economic and regulatory landscape of Southeast Asian markets. In the practical part, a multi-criteria scoring model is applied to assess and rank countries based on key indicators relevant to blockchain entrepreneurship (such as business climate, digital infrastructure, and regulatory environment). Furthermore, a SWOT analysis is conducted for the top-ranked countries to examine their internal strengths and weaknesses and external opportunities and threats. These quantitative methods are complemented by in-depth interviews with blockchain entrepreneurs, whose insights help to contextualize the region’s opportunities and challenges. The analysis identifies Singapore, Malaysia, and Thailand as the three most promising countries for blockchain startup ventures in Southeast Asia. Finally, the thesis provides recommendations and highlights the strategic importance of choosing the right location, offering valuable guidance for blockchain entrepreneurs and policymakers in the region.
Vedoucí práce: Kareem Issam Abdallah
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses